LEGAL AND PRACTICAL IMPLICATIONS OF THE ICJ ON SOUTH AFRICA'S LAWSUIT AGAINST ISRAEL REGARDING PALESTINE - Irianto, khairunnisa (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2024)
The International Court of Justice's temporary ruling on South Africa's lawsuit against Israel and Palestine asks Israel to take all steps to prevent genocide in the vast territory of the Gaza Strip. Israel must also prevent and punish those who publicly incite genocide in Gaza and increase the inflow of humanitarian aid to residents. The aim of this research is to examine the legal implications and impacts of the temporary decision of the International Court of Justice (ICJ). As well as its practical implications in efforts to achieve peace and justice in the region. The conclusions of this research provide in-depth insight into the relevance of international law in resolving the long-standing political and humanitarian tensions between Palestine and Israel.